Pulmonary and Cardiorenal Cyclooxygenase-1 (COX-1), -2 (COX-2), and Microsomal Prostaglandin E Synthase-1 (mPGES-1) and -2 (mPGES-2) Expression in a Hypertension Model - Zaher A. Radi; Robert Ostroski (Hindawi Limited, 2007)
Hypertensive mice that express the human renin and angiotensinogen genes are used as a model for human hypertension because they develop hypertension secondary to increased renin-angiotensin system activity. Our study investigated the cellular localization and distribution of COX-1, COX-2, mPGES-1, and mPGES-2 in organ tissues from a mouse model of human hypertension. Male (n=15) and female (n=15) double transgenic mice (h-Ang 204/1 h-Ren 9) were used in the study. Lung, kidney, and heart tissues were obtained from mice at necropsy and fixed in 10% neutral buffered formalin followed by embedding in paraffin wax. Cut sections were stained immunohistochemically with antibodies to COX-1, COX-2, mPGES-1, and mPGES-2 and analyzed by light microscopy. Renal expression of COX-1 was the highest in the distal convoluted tubules, cortical collecting ducts, and medullary collecting ducts; while proximal convoluted tubules lacked COX-1 expression. Bronchial and bronchiolar epithelial cells, alveolar macrophages, and cardiac vascular endothelial cells also had strong COX-1 expression, with other renal, pulmonary, or cardiac microanatomic locations having mild-to-moderate expression. mPGES-2 expression was strong in the bronchial and bronchiolar epithelial cells, mild to moderate in various renal microanatomic locations, and absent in cardiac tissues. COX-2 expression was strong in the proximal and distal convoluted tubules, alveolar macrophages, and bronchial and bronchiolar epithelial cells. Marked mPGES-1 was present only in bronchial and bronchiolar epithelial cells; while mild-to-moderate expression was present in other pulmonary, renal, or cardiac microanatomic locations. Expression of these molecules was similar between males and females. Our work suggests that in hypertensive mice, there are (a) significant microanatomic variations in the pulmonary, renal, and cardiac distribution and cellular localization of COX-1, COX-2, mPGES-1, and mPGES-2, and (b) no differences in expression between genders.